The Potential Consequences of Alternative Exchange Rate Regimes: A Study of Three Candidate Regions - Eduard Hochreiter; Anton Korinek; Pierre L. Siklos (Oesterreichische Nationalbank (OeNB), 2002)
The paper examines the macroeconomic consequences of selecting alternative exchange rate regimes of countries in three regions. In particular, it studies whether Austria, the Netherlands, Canada and New Zealand made the right monetary regime choices between 1970 and 2000. We focus on the role of asymmetric shocks as a core determinant for the evaluation of various monetary regimes by studying the impact of a hard peg, a full monetary union, or floating exchange rates (with or without inflation targeting) on selected macroeconomic variables. Estimates of structural VARs are used to ascertain if the countries under review meet the essential ingredients of an optimum currency area (OCA) and thus are candidates for a monetary union. Counterfactual experiments help to study economic outcomes had these countries pursued alternative monetary strategies. We conclude that a floating regime with inflation targeting is best for Canada, a monetary union with Australia is the best course of action for New Zealand, and monetary union is the appropriate choice for the Netherlands while there are reasons to believe that Austria might have been better off with a floating regime, at least for a time. We also find that good monetary policy is not confined to any particular exchange rate regime and that political and institutional factors weigh heavily in this decision.
Keywords: E30; F30; 330; Exchange rate regimes; Monetary Union; SVARs